Infection of Cyclospora cayetanensis in Diarrhoeal Children of Nepal - Sherchan, Jatan B; Sherpa, Kunjang; Tandukar, Sarmilla; Cross, John H; Gajadhar, Alvin; Sherchand, Jeevan B (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Introduction: Cyclospora cayetanensis is a coccidian parasite that causes recurrent gastroenteritis among children living under poor sanitary condition and adults from industrialized countries who lived or traveled in endemic developing countries. Methods: A total of 1842 stool specimens from gastroenteritis patients were examined between March 2006 to February 2007 and collected various types of faecal specimens from human, animals and samples of water and green leafy vegetables. Results: Of 1842 stool specimens collected from different areas of Nepal, 146 (7.9 %) were found to be positive for Cyclospora cayetanensis. with the majority were from children 2-9 years of age. The highest rate of infections was found in the month of June; (31.6%). Cyclospora cayetanensis were found to be contaminated in green vegetables including leaves of basil, mint leaves, water sources and feces of domestic animals and these findings were presented in the paper. Conclusion: Cyclospora-like oocysts were detected in vegetables leaves, feces of domestic animals and water sources. The results suggest that water, vegetables and domestic animals are possible sources of infection in Nepal. The study also obtained more information on Cyclospora cayetanensis a coccidian parasite that infect humans especially children and causes prolonged diarrhea and life threatening infestation. Key words: Cyclospora cayetanensis, source, Nepal DOI: 10.3126/jnps.v30i1.2456 Journal of Nepal Paediatric Society Vol.30(1) 2010 23-30